The Frailty, Fitness, and Psychophysical/Social Condition of Community-Dwelling Older Adults—Analysis of 5-Year Longitudinal Data - Emi Yamagata; Yuya Watanabe; Miwa Mitsuhashi; Hidemi Hashimoto; Yuriko Sugihara; Naoko Murata; Mitsuyo Komatsu; Naoyuki Ebine; Misaka Kimura (Geriatrics)
Background/Objectives: Frailty is a multifactorial condition influenced by physical and psychosocial factors. Understanding longitudinal changes in these domains may guide prevention strategies. This study examines the relationship between frailty status, physical fitness, and psychosocial conditions in community-dwelling older adults using five-year longitudinal data. Methods: Participants were 52 out of 89 older adults who completed both baseline and five-year follow-up assessments (follow-up rate: 58.4%). Data were collected using 10 physical fitness indicators, the fitness age score (FAS), geriatric depression scale (GDS), Lubben social network scale short form (LSNS-6), and relevant items in the six Kihon Checklist (KCL) domains. Due to low prevalence of frailty, individuals with pre-frailty and frailty were combined into the frailty-risk group. Repeated measures ANOVA with sex as a covariate was conducted to compare groups. Logistic regression was used to identify baseline predictors of frailty status at five years. Statistical significance was set at p < 0.05. Results: GDS, LSNS-6, and KCL scores remained stable over five years. However, physical fitness significantly declined in several measures, including grip strength, vertical jump height, knee extension strength, functional reach, and FAS. A significant interaction for the timed up and go test showed that the robust group maintained function, while the frailty-risk group declined. Logistic regression identified KCL oral function as a significant predictor (OR = 5.331, 95% CI = 1.593–17.839, p = 0.007). Conclusions: Maintaining both oral function and physical fitness is vital for preventing frailty, even among health-conscious older adults. Proactive strategies may support healthy aging.